Formation of the stress state of the concrete support during shaft sinking - Shardakov, Igor’ Nikolayevich; Shestakov, Aleksey Petrovich; Glot, Irina Olegovna; Epin, Valeriy Valer’yevich; Gusev, Georgiy Nikolayevich; Tsvetkov, Roman Valer’yevich (Computational Continuum Mechanics, 2023)
Shaft sinking is a safety-related and high-priced procedure. In the process of sinking, emergencies may occur. To prevent their occurrence, it is necessary to reliably assess the stress state of the mine shaft support at the design stage. This problem can be solved using mathematical modeling methods. The level of their reliability depends on the accuracy of the description of the technological process and the mechanical behavior of the soil. The paper presents the result of numerical simulation of a step-by-step process of vertical shaft sinking using two technological schemes. According to the first scheme, concreting is performed up to the current position of the shaft bottom. According to the second scheme, concreting lags behind excavation by one sinking step. Modeling of the sinking process is carried out in the case of rock salt mining. The shaft diameter is 10 meters, the step and depth of sinking are 5 and 1000 meters, respectively. Soil modeling is performed using three variants of physical relations, which makes it possible to estimate the role of soil deformation at the unloading stage. The paper analyzes the stress-strain state of the mine shaft in the process of its reinforcement by concrete lining with an emphasis on the assessment of normal stresses in the direction of the vertical axis that occur in the support during sinking. The following conclusions are drawn from the obtained results: the value of maximum tensile stress of the support calculated for the first sinking scheme is about 13 times higher than the similar value obtained for the second scheme; taking into account the elastic characteristics of the soil, typical for the unloading stage, changes the value of the maximum tensile stresses of the support by more than two times. The possibility of the formation of horizontal cracks in the support is investigated depending on the method of shaft sinking and soil deformation model. It follows from the analysis that the appearance of the first cracks in the concrete support can be detected at the depth of ≈ 40 meters for the first scheme of sinking and at the depth of ≈ 450 meters for the second scheme.